PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS X SMA RIYADLUL JANNAH, CISEENG, BOGOR - Hidayatulloh, Syarif (Inspiratif Pendidikan, 2021)
This study aims to determine the description of the use of the Cooperative Script learning model and determine student learning outcomes after using the Cooperative Script learning model in Islamic Religious Education learning for class X students of SMA Riyadlul Jannah, Ciseeng, Bogor for the academic year 2020/2021. The method used in this research is descriptive qualitative with research data sources, namely the results of observations made by the author and written tests (pre-test and post-test) conducted by students of class X SMA Riyadhul Jannah.The results showed that the use of cooperative script learning model can help students be more active during the learning process. This can be seen from the percentage of active student observations which increased significantly from 27% to 90%. In addition, the use of the cooperative script learning model can help improve student learning outcomes. This can be seen from the achievement of mastery student learning outcomes before using the cooperative script learning model only reached 25% while after using the cooperative script learning model it reached 90% with the average value before using the cooperative script learning model, which was 62.75, while after using the cooperative script learning model, the average score was 62.75. cooperative script learning is 84.25. Thus, this proves that the cooperative script learning model is effective in increasing student activity in class and can improve student learning outcomes for class X SMA Riyadhul Jannah, Ciseeng, Bogor.